MODEL INTERVENSI PASTORAL KONSELING UNTUK PEMULIHAN EMOSIONAL ANAK KORBAN PERCERAIAN - Lisa Sariowan (MATHESI: Jurnal Pendidikan dan Bimbingan Konseling, 2026)
Pastoral counseling is a form of church ministry that focuses on accompanying congregants in facing emotional, spiritual, and relational struggles. This article aims to examine the relational approach and intervention techniques employed in church-based pastoral counseling practices. The relational approach emphasizes the importance of authentic, empathetic, and trust-based relationships between the pastoral counselor and the counselee as the fundamental foundation of the counseling process. Through healthy relationships, counselors are able to understand the counselee’s life experiences holistically and assist them in finding meaning and restoration in the light of Christian faith. This study employs a literature review method by analyzing relevant sources in pastoral theology and counseling. The findings indicate that the application of intervention techniques such as active listening, emotional reflection, spiritual guidance, pastoral prayer, and ongoing accompaniment plays a significant role in supporting the healing process and the growth of congregational faith. This article affirms that the integration of a relational approach and contextual intervention techniques is key to the effectiveness of church pastoral counseling in addressing congregational needs comprehensively.